Eating disorders among Moroccan medical students: cognition and behavior - Azzouzi N; Ahid S; Bragazzi NL; Berhili N; Aarab C; Aalouane R; Boujraf S; Rammouz I (Psychology Research and Behavior Management, 2019)
Nada Azzouzi,1 Samir Ahid,2 Nicola Luigi Bragazzi,3–5 Nabil Berhili,1 Chadya Aarab,1 Rachid Aalouane,1 Said Boujraf,1 Ismail Rammouz1 1Laboratory of Clinical Neurosciences, Medical and Pharmacy School, Sidi Mohammed Ben Abdellah University, Fez, Morocco; 2Laboratory of Epidemiological and Clinical Research, Medical and Pharmacy School, Mohammed V University of Rabat, Rabat, Morocco; 3Department of Health Sciences (DISSAL), School of Public Health, University of Genoa, Genoa, Italy; 4Department of Neuroscience, Rehabilitation, Ophthalmology, Genetics, and Maternal and Child Health (DINOGMI), Section of Psychiatry, Genoa University, Genoa, Italy; 5GESTALT Study Center (CSTG), Milan, Italy Introduction and aim: Eating disorders (EDs) are complex, multifactorial diseases linked to biological, developmental, psychological, and sociocultural factors. Medical students are among subjects at high risk of EDs. The aim of the present investigation was to evaluate EDs among 710 Moroccan medical students with a focus on cognition and behavior related to EDs. Methods: Sociodemographic, economic, and clinical data were collected. Validated questionnaires, such as the SCOFF (Sick, Control, One Stone, Fat, Food) questionnaire and the Eating Disorder Inventory 2 (EDI2), were administered. Results: The male:female ratio was 0.53, mean age was 21±2 years, 11.1% of participants were underweight, 13.4% were overweight, and 1.8% were obese. A middle socioeconomic level was found in 84.9% of cases. The prevalence of EDs in students was 32.8% (37.6% among females and 23.7% among males) and that of weight-control behaviors 18.5%. Increased body-mass index values were significantly associated with dieting (P<0.001), fasting (P=0.044), and the use of appetite suppressants (P=0.037). Conclusion: It appears that the impact of EDs is high, affecting a third of medical students, with significant use of harmful weight-control behaviors. We also found that dimensions of bulimia, perfectionism, body dissatisfaction, and ineffectiveness, parts of the core of EDs, were found in future medical practitioners. Keywords: eating disorders, cultural factors, medical students, screening, body image, body-mass index